2019
DOI: 10.1016/j.ijrobp.2019.04.032
|View full text |Cite|
|
Sign up to set email alerts
|

Evolution and Dosimetric Analysis of Magnetic Resonance Imaging–Detected Brain Stem Injury After Intensity Modulated Radiation Therapy in Nasopharyngeal Carcinoma

Abstract: Evolution of brain stem injury (BSI) after intensity modulated radiation therapy and related dose constraints have not been well defined in a large cohort of nasopharyngeal carcinoma. Through longitudinal follow-up Purpose: To evaluate the evolution of radiation-induced brain stem injury (BSI) in patients with nasopharyngeal carcinoma (NPC) treated with intensity modulated radiation therapy (IMRT) and to identify the critical dosimetric predictors of BSI. Methods and Materials: A total of 6288 NPC patients tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Huang et al. showed that patients submitted to a brainstem Dmax <67.4 Gy had a significantly lower risk of developing brainstem injury than those with a Dmax ≥67.4 Gy (OR = 25.29, 95% CI: 8.63–74.14; P < 0.001) ( 41 ); indicating that a brainstem Dmax <67.4 Gy can be safe and effective for patients with NPC receiving IMRT treatment. Taken together, these data suggest that the radiation tolerance of these intracranial structures should be reassessed for IMRT treatment planning.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al. showed that patients submitted to a brainstem Dmax <67.4 Gy had a significantly lower risk of developing brainstem injury than those with a Dmax ≥67.4 Gy (OR = 25.29, 95% CI: 8.63–74.14; P < 0.001) ( 41 ); indicating that a brainstem Dmax <67.4 Gy can be safe and effective for patients with NPC receiving IMRT treatment. Taken together, these data suggest that the radiation tolerance of these intracranial structures should be reassessed for IMRT treatment planning.…”
Section: Discussionmentioning
confidence: 99%
“…RBN is a serious complication of intracranial and skull base tumors after radiotherapy. Previous studies included data on the frequency of RBN after irradiation of nasopharyngeal carcinoma (NPC), glioma, brain metastases, and intracranial arteriovenous malformations and are summarized in Table 1 [6][7][8][9][10][11][12][13][14][15]. Ruben et al [15] have reported that adjuvant chemotherapy after radiotherapy increased the incidence of RBN by a factor of five.…”
Section: Epidemiologymentioning
confidence: 99%
“…Yet, several studies have reported that the incidenceof RIBN can be significantly reduced when using IMRT. For example, a retrospective study showed that only 0.13–2.8% [ 10 12 ] of patients with NPC developed brainstem necrosis after IMRT. RIBN is a late complication with low incidence but still worth of attention.…”
Section: Introductionmentioning
confidence: 99%
“…In the IMRT era, radiotherapist are usually confused by the tolerance dose of the brainstem, while the dose limit of conformal radiotherapy for the brainstem has been well-established [ 13 ]. Huang et.al reported a total of 24 BSI in 6288 patients who underwent IMRT and suggested a Dmax of 67.4 Gy (D2) as the dose constraint for brain stem [ 12 ]. However, the author also admitted that this was not ideal because it had relatively poor positive predictive value [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation